Short-term treatment of golden retriever muscular dystrophy (GRMD) dogs with rAAVrh74.MHCK7.GALGT2 induces muscle glycosylation and utrophin expression but has no significant effect on muscle strength. - Paul T Martin; Deborah A Zygmunt; Anna Ashbrook; Sonia Hamilton; Davin Packer; Sharla M Birch; Amanda K Bettis; Cynthia J Balog-Alvarez; Lee-Jae Guo; Peter P Nghiem; Joe N Kornegay (PLoS ONE)
We have examined the effects of intravenous (IV) delivery of rAAVrh74.MHCK7.GALGT2 in the golden retriever muscular dystrophy (GRMD) model of Duchenne Muscular Dystrophy (DMD). After baseline testing, GRMD dogs were treated at 3 months of age and reassessed at 6 months. This 3-6 month age range is a period of rapid disease progression, thus offering a relatively short window to establish treatment efficacy. Measures analyzed included muscle AAV transduction, GALGT2 transgene expression, GALGT2-induced glycosylation, muscle pathology, and muscle function. A total of five dogs were treated, 4 at 2x1014vg/kg and one at 6x1014vgkg. The 2x1014vg/kg dose led to transduction of regions of the heart with 1-3 vector genomes (vg) per nucleus, while most skeletal muscles were transduced with 0.25-0.5vg/nucleus. GALGT2-induced glycosylation paralleled levels of myofiber vg transduction, with about 90% of cardiomyocytes having increased glycosylation versus 20-35% of all myofibers across the skeletal muscles tested. Conclusions from phenotypic testing were limited by the small number of dogs. Treated dogs had less pronounced fibrosis and overall lesion severity when compared to control groups, but surprisingly no significant changes in limb muscle function measures. GALGT2-treated skeletal muscle and heart had elevated levels of utrophin protein expression and GALGT2-induced expression of glycosylated α dystroglycan, providing further evidence of a treatment effect. Serum chemistry, hematology, and cardiac function measures were largely unchanged by treatment. Cumulatively, these data show that short-term intravenous treatment of GRMD dogs with rAAVrh74.MHCK7.GALGT2 at high doses can induce muscle glycosylation and utrophin expression and may be safe over a short 3-month interval, but that such treatments had only modest effects on muscle pathology and did not significantly improve muscle strength.